Knowledge Regarding Breast Cancer among Female Community Health Volunteers of Gorkha District - Sharma, Sarojini; Basnet, Nikita; Upadhyay, Hari Prasad; Neupane, Laxmi (International Journal of Silkroad Institute of Research and Training, 2025)
Background: Breast cancer is the most common cancer in women. The disease's burden is particularly acute in developing nations due to both high incidence and mortality rates, and a projected increase in cases is expected due to aging populations and lifestyle factors. Method: A Research study on “Knowledge regarding Breast Cancer Among Female Community Health Volunteers of Gorkha district” was conducted to assess knowledge of breast cancer. To understand and recognize the key aspects related to breast cancer, including its risk factors, signs, symptoms, preventive measures, and available treatments. One hundred female community health volunteers working in Gorkha municipality and Sahid Lakhan rural municipality were selected as the study sample by using a non-probability purposive sampling technique. Data were collected using a structured questionnaire and analyzed using descriptive and inferential statistics. Result: Findings of the study revealed that 35.0% of respondents were in the age group of 40-49. Similarly, 34% of respondents were in the 50-59 age group. Likewise, 27% respondents were in the age group of 30-39, while a few (4.0%) were in the 20-29 age group. Regarding marital status, 97.0% of the respondents were married and few (2.0%) of respondents were widow and 1.0% unmarried respectively. Regarding educational status, more than half (54.0%) of the respondents had primary education, and a few (2.0%) had bachelor's degrees or higher. Regarding religion, most (89.0%) were Hindu, and only 1% was Christian. Findings of the study revealed that two-thirds of the respondents (67%) had a poor level of knowledge, 17% had a good level of knowledge, and 16% had a moderate level of knowledge regarding breast cancer. Conclusion: Based on the findings of the study, it is concluded that female community health volunteers had a poor level of knowledge regarding breast cancer. So, there is a need for training and education regarding breast cancer for female community health volunteer as they are actively engaged within their communities for awareness creation and health promotional activities.